DAYA SAING INDUSTRI KACANG GOYANG DI KOTAMOBAGU (STUDI KASUS DI USAHA DAGANG BERUSAHA DAN USAHA DAGANG KABELA) - Windy Amelia Makakombo; Leonardus R. Rengkung; Celcius ., Talumingan (Sam Ratulangi University, 2016)
The purpose of this study is to analyze the Competitivences of ‘Kacang Goyang’ industry of ‘UD Berusaha’ and ‘UD Kabela’ Kotamobagu, North Sulawesi. This study was conducted over three months from July to October 2015 in Motoboi Kecil, South Kotamobagu, North Sulawesi. Data used in this study are primary and secondary data. Primary data collection is done by interview using questionnaires and secondary data derived from Dinas Pertanian. The used analysis is Importance Performance Analysis (IPA). The result showed that consumers are satisfied with the level of the cleanliness, appearance and performance. Prices offered by the two businesses are affordable and is according to the contents of products and flavors. The consumen is satisfied with the price. Consumers’ considended that the two companies have a clean and comfortable place, but there are some aspects that should be corrected such as, location and parking. Consumers also considened that this two companies provide a good service in the aspect of speed, knowledge and friendliness, but consumers have not been satisfied in the physical aspect, dressed, and neatness.*lrr*